A convenient method for preparing rigid-core ionic liquid crystals - Fouchet, Julien; Douce, Laurent; Heinrich, Benoît; Welter, Richard; Louati, Alain (Beilstein Journal of Organic Chemistry, 2009)
An efficient, solvent free method for the N-arylation of imidazole by 1-(dodecyloxy)-4-iodobenzene using Cu(II)-NaY as catalyst and K2CO3 as base is reported. By this synthetic approach, mesomorphic 3-[4-(dodecyloxy)phenyl]-1-methyl-1H-imidazol-3-ium iodide was synthesized in a two-step procedure, and its mesomorphism has been fully investigated by polarised optical microscopy, differential scanning calorimetry and X-ray diffraction. In addition its lamellar crystal structure, electrochemical behaviour and UV (absorption and emission) properties are reported.
Keywords: imidazolium; ionic liquid crystals; Ullman reaction